Fecal Calprotectin: A Comprehensive Systematic Review of Its Diagnostic and Monitoring Efficacy in Inflammatory Bowel Disease - Emilia Fitri Annisa; Charles Sanjaya (International Medical Journal Corp. Ltd, 2025)
Introduction Inflammatory Bowel Disease (IBD), encompassing Ulcerative Colitis (UC) and Crohn's Disease (CD), is a chronic, relapsing condition demanding continuous, objective surveillance of mucosal inflammation. Due to the burdens associated with invasive endoscopy—the conventional gold standard for assessment—there is a critical need for accurate, non-invasive biomarkers. Fecal Calprotectin (FC), a stable protein released by activated neutrophils, serves as a quantitative surrogate marker that directly correlates with the level and extent of gastrointestinal inflammation. This comprehensive systematic review aggregates high-level meta-analytic evidence to define the precise utility of FC across IBD diagnosis, therapeutic monitoring, and prediction of long-term disease course. Methods This systematic review synthesized quantitative findings from high-quality diagnostic accuracy and prognostic meta-analyses, encompassing data pooled from over fifteen primary studies focusing on adults and children with IBD. The underlying systematic searches utilized extensive database coverage, including PubMed, Google Scholar, Semantic Scholar, Springer, Wiley Online Library. Key performance metrics rigorously extracted included pooled sensitivity, specificity, Area Under the Summary Receiver Operating Characteristic Curve (AUROC), Diagnostic Odds Ratio (DOR), Positive Likelihood Ratio (PLR), and Negative Likelihood Ratio (NLR). The methodological rigor of the aggregated evidence was assessed using the QUADAS-2 framework. Results FC demonstrated superior accuracy for differentiating IBD from functional gastrointestinal disorders. At the standard 50 mug/g cut-off, pooled analyses yield high sensitivity (89% to 99%) and a critically high Negative Predictive Value (NPV) of 0.99 for IBD exclusion. In monitoring, FC reliably correlates with endoscopic activity, with optimal performance in UC (AUROC 0.97) but diminished utility in isolated small bowel CD (SB-CD), where the AUROC drops to 0.72 at the 100 mug/g cut-off. For prognostic assessment, the optimal pooled cut-off of 152 mug/g for predicting clinical relapse in adult UC patients in remission yields a robust DOR of 10.54. Furthermore, distinct concentration ranges define Mucosal Healing (MH) targets: 60-75 mug/g for UC (AUC 0.88) versus a higher 180-250 mug/g range for CD (AUC 0.79). Discussion FC is confirmed as an essential biomarker, yet its optimal implementation requires careful consideration of its limitations, including significant quantitative variability (up to 5-fold differences) across commercial assays, which hinders the universal application of precise meta-analytic thresholds. The physiological barrier in detecting proximal small bowel inflammation necessitates integrating FC results with cross-sectional imaging and exploring complementary serum biomarkers. The greatest clinical value of FC lies in its use for continuous, longitudinal surveillance to proactively guide therapeutic intensification and reduce the need for unnecessary endoscopic procedures. Conclusion and Recommendations Fecal Calprotectin is established as an indispensable, non-invasive biomarker for IBD triage and continuous surveillance. Its clinical efficacy is maximized through the meticulous application of phenotype- and location-specific cut-offs tailored to the specific clinical query (diagnosis, MH, or relapse prediction). Standardizing commercial FC assays remains the most crucial outstanding challenge to ensure the consistent, reliable, and interchangeable application of these evidence-based thresholds across global healthcare settings.